Teachers’ perspective on student’s right to participation in classroom management / Muhammad Thoyibi, Mauly Halwat Hikmat and Aryati Prasetyarini - Thoyibi, Muhammad; Hikmat, Mauly Halwat; Prasetyarini, Aryati (Universiti Teknologi MARA, 2021)
The study aimed at exploring the teachers’ perspective on the right of the child to participate in the seating arrangement and how the teachers resolved when values and norms were in conflict. The data were collected through questionnaires by a convenience sampling technique from seven regencies in Central Java and East Java, Indonesia. The participants of the research were teachers at Junior High Schools and Senior High Schools. The results of the study showed the following findings. Firstly, 81% of the teachers stated that the students have the right to choose their own seats. However, half of the teachers excluded the rights of the students to choose with whom they sat. Secondly, practices in different schools, especially private and Islamic schools, demonstrated that religious norms played such a significant role in the school and classroom management. It indicates that the values derived from the legal sources were subject to the aim of complying with the religious norms.